تأثير برنامج (ارشادي – تعليمي) في خفض ألتوتر النفسي وتعلم اداء بعض المهارات ألفنية بالكره الطائرة (Journal of the College of Basic Education, 2025)
Introduction to research and its importance / Guidance helps in building the personality of the individual, which leads to a better life by helping them to draw future plans that suit them and that its purpose is to clarify the ideas they make and then used as a source of correcting mistakes and exchanging opinions and ideas with others, and that the game of flying ball is one of the widely practiced and interesting sports games and is implemented with its defensive and offensive skills as it is learned and mastered highly, so the guidance program is necessary to use it in the fieldEducational, hence the importance of the research lies in identifying the extent of the impact of the (guiding - educational) program by reducing stress and learning to perform some skills. As for the problem of researching through the researcher's experience, being a school for volleyball, I found a change in the behavior of students, as they show confusion, tension and a lot of emotions that appear in students when performing skills, which leads to failure in skill performance, so the researcher decided to know the reason for this and the emergence of the following question: - What is the effect of the educational guidance program by reducingStress and learn to perform some technical skills on the sample, and the research aims to identify the impact of the guidance program -My education is to reduce stress and learn to perform some technical skills with flying ball, and it is assumed that the guidance program